2014
DOI: 10.1128/genomea.00718-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of 228 Shiga Toxin-Producing Escherichia coli Isolates and 12 Isolates Representing Other Diarrheagenic E. coli Pathotypes

Abstract: Shiga toxin-producing Escherichia coli (STEC) are a common cause for food-borne diarrheal illness outbreaks and sporadic cases. Here, we report the availability of the draft genome sequences of 228 STEC strains representing 32 serotypes with known pulsed-field gel electrophoresis (PFGE) types and epidemiological relationships, as well as 12 strains representing other diarrheagenic E. coli pathotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 2 publications
0
14
1
Order By: Relevance
“…JHGK00000000 ), 2009C-4826 (GenBank accession no. JHGI00000000 ), ( 44 ), and CFSAN001629 (GenBank accession no. AMXO00000000 ) ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…JHGK00000000 ), 2009C-4826 (GenBank accession no. JHGI00000000 ), ( 44 ), and CFSAN001629 (GenBank accession no. AMXO00000000 ) ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that these isolates had identical PFGE band, but their differences were revealed by sequencing. Likewise, Trees et al [17] sequenced 240 isolates related to outbreaks from different sources by PFGE fingerprinting. As a result, whole genome sequencing of 228 isolates showed that they were Shiga toxin-producing E. coli, whereas other 12 isolates were non-Shiga toxin-producing diarrheagenic E. coli.…”
Section: Convergence Of E Coli Isolatesmentioning
confidence: 99%
“…Of these, 249 were assembled genomes from the PulseNet STEC genome reference library, deposited by the Centers for Disease Control and Prevention (CDC), Atlanta, GA (accession no. PRJNA218110), and 130 were genome sequences included in a previous study on comparative genome analysis of E. coli (19,20). Four Shigella genomes were available and included from this study.…”
Section: Methodsmentioning
confidence: 99%